Políticas de focalización educativa en tiempos de inclusión educativa: el caso de las escuelas primarias de jornada extendida en la provincia de Río Negro, República Argentina - Silvia Noemi Barco (2014)
This study interrogates the Extended-Day Policy in Primary Schools of the Province of Rio Negro, Argentina, between 2006-2013. This Policy is identified as an Educational Targeting measure that seeks to promote the schooling of children defined as a vulnerable population, and is reinforced in a juncture in which both the goal of Educational Inclusion and the conception of Education as a Social Right are present in discourses and regulations. The concern that guides the focus of this research is centered in the analysis of the measures intended to oversee, within the sphere of public educational institutions, the relation poverty - education, namely the inquiry regarding the kind of education intended for the subordinate classes / sectors. The research problem interrogates the theoretical, political and pedagogical conceptions and orientations that define the goals, purposes and contents of the Extended-Day Schools Policy and the assessments and evaluations from school managers, teachers, parents and students regarding the policy and its results. The general aims seek to understand both the Policy as a State measure macropolitical level identifying the contents, goals and values underlying its design and implementation, as well as the practices and results in schools micropolitical level. The theoretical perspective is inscribed within the field of critical theory, interpreting poverty and social inequality as structural problems in a capitalistic society affected by contradictions and antagonistic class interests. A qualitative methodological focus is applied, prioritizing the goal of understanding, the discovery context and the process of generative research centered in the identification of categories and propositions, based on empirical information. The macropolitical aspects were studied by reviewing a corpus of secondary sources from the studied time period and conducting 4 key informant interviews. We selected 5 Extended-Day Primary Schools, located in the provinces Valley or Plateau regions. During 8 months, we conducted 22 in-depth interviews and several observations and institutional documentary analyses. The epistemological and methodological decisions, the field work and the analysis and systematization of the information surveyed seek to achieve a comprehension of the reality understood as a structured and dialectic whole, in which the social fact is configured as a structuring part of the whole (KOSIK, 1984).